The luteolytic effect and pregnancy rate of luprostiol, administrated via different routes and various doses in heifers - Mehmet Güler; D. Ali Dinç; Ahmet Semacan; Melih Aksoy; Kürşat Işık; Hüseyin Erdem (Eurasian Journal of Veterinary Sciences)
In this study, the luteolytic effect and pregnancy rate of Luprostiol administrated via different routes and various doses in heifers were investigated. Animals were divided info three experimental groups, each inc!uding 5 heifers. Group 1 (intra muscular group, (IMG), Group II (intravulvo-submucozal group, IVSMG), Group III (intra ovarian group, lOG), were treated with 15 mg, 3, 75 mg and 0.75 mg Luprostiol respectively. Luteoliytic response was monitored by measuring plasma progesterone concentration. One animal specimen in each group has not s ho wed any evidence of luteolysis while luteolysis in the rest of the animals in IM and IO groups, there was a delay in luteolysis in two animals in IVSM group. Plasma progesteron levels decreased less than 1 ng/ml within 24 hours after PGF2α administration in IM and /0 groups (0.22±0. 18, 0.74±0.39, respectively), however, it was found higher in IVSM group (0.80±0.55 ng/ml) compared to others. The appearance of estrous detected through visual observation was between 49-72 hours in IM and IVSM groups, whereas it was observed earlier (24-36 hours) in IO group. All animals showed estrus, artiiicialIy insemineted, of which the IO group had the highest pregnancy rat e of 100%.